Perovskite Ceramics : Recent Advances and Emerging Applications - Clabel Huaman, Jose Luis; Rivera, Victor Anthony Garcia (Elsevier Series in Advanced Ceramic Materials, 2023)
Perovskite-based ceramics are a significant class of innovative materials with fascinating physical properties, which are now receiving intensive research attention in condensed matter physics and in the area of practical device applications. Perovskite Ceramics provides a state-of-the-art review on the latest advances in perovskite-based ceramic materials, as well as the development of devices from these materials for different applications. Perovskite Ceramics: Recent Advances and Emerging Applications is divided into two main parts. The first part focuses on the basics of perovskite-based ceramic materials and includes chapters on the fundamentals, synthesis and processing, characterization, and properties of these materials. Chapters are also included on bulk and thin materials, phase transitions, polaronic effects and the compensation and screening of ferroelectricity. This section will allow the reader to familiarize themselves with the standard traditional approach, but it will also introduce new concepts that are fast evolving in this field. The second part presents an extensive review of up-to-date research on new and innovative advances in perovskite-based ceramic materials. Chapters cover multiferroic applications, lead-free perovskites, energy storage applications, perovskite-based memories, light manipulation and spectral modifications, and solar cells and fuel cells. All these fields of research are rapidly evolving, so the book acts a platform to showcase latest results on optical strategies and materials for light manipulation, and spectral up- and down-conversion too (mainly rare earth doped oxides and complexes). The book will be an essential reference resource for academic and industrial researchers working in materials research and development particularly in functional and oxide ceramics and perovskites.